Effect of the Heusler phase formation on the magnetic behavior of the Cu-10 wt.%Mn alloy with Al and Ag additions - Carvalho, T. M. [UNESP]; Adorno, A. T. [UNESP]; Santos, C. M A [UNESP]; Silva, R. A G; Magnani, M. [UNESP] (Elsevier, 2015)
In this work, the formation of the Cu2AlMn Heusler phase and its influence on the magnetic behavior of the Cu-Mn-Al-Ag alloys in the range of 8-10 wt.% of aluminum and 2-4 wt.% of silver were studied using differential scanning calorimetry (DSC), transmission electron microscopy (TEM), high-resolution TEM (HRTEM) and saturation magnetization measurements at 4 K. The results showed that there is a correlation between the presence of the Ag-rich phase and the formation of the Cu2MnAl phase.
Keywords: Magnetic measurements; Metals and alloys; Microstructure; Precipitation; Solid state reactions